(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate the prevalence of sleep disturbance and glycemic control among patients with type 2 diabetes, and to evaluate the association between sleep quality (PSQI) and HbA1C. Methods: A cross-sectional study was conducted among 171 outpatients with type 2 diabetes at Hue University of Medicine and Pharmacy Hospital. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality, and HbA1C was used as an indicator of glycemic control. Logistic regression analysis was performed to explore the association. Results: 60.7% of participants had poor sleep quality (PSQI ≥ 5). Among them, 38.7% had uncontrolled HbA1C (≥ 7%). Logistic regression revealed that PSQI ≥ 5 was an independent predictor of poor glycemic control (OR = 2.32; 95% CI: 1.09–4.95; p = 0.029). Conclusion: Sleep disturbance is prevalent and significantly associated with poor glycemic control among patients with type 2 diabetes. Screening and management of sleep disorders should be considered as an integral part of diabetes care.